Flume Tests to Investigate the Initiation Mechanism of Loess Mudflows on the Chinese Loess Plateau - Ma, Penghui; Zhuang, Jianqi; Zhu, Xinghua; Cheng, Yuxiang; Liu, Cong (Frontiers in Earth Science, 2021)
Loess has a strong water sensitivity, so loess landslides often transform into loess mudflows when water is added on the Chinese Loess Plateau, which results in high casualties and property loss of the Chinese government. In this study, a series of flume tests were designed to study the initiation of loess mudflows. The results reveal that the initiation modes of loess mudflows include large-scale mudflow and retrogressive toe sliding (Type A), and small-scale mudflow and retrogressive toe sliding (Type B). A model was used to analyze the test results that describe the effects of water flow on the potential for hillslope failure and liquefaction. It was found that the soil accumulation was unconditionally stable before a loess mudflow was formed, but as the rainfall continued, the water gradually infiltrated the soil, and the soil accumulation changed from unconditionally stable to unconditionally unstable. Thus, this led to different initiation modes during the tests. For Type A, the water preferentially infiltrated into the area with an uneven density and a large amount of water accumulated. The pore water pressure increased quickly and could not dissipate in time, so the loess liquefied. As the liquefaction area continued to expand and became larger, Type A occurred. Relatively speaking, Type B occurs in soil accumulations with relatively uniform densities. These results provide a certain scientific reference for the study of loess mudflows.